Prevalence of musculoskeletal pain and level of postural awareness among varsity students / Fairus Fariza Zainudin ... [et al.] - Zainudin, Fairus Fariza; Abdullah, Siti Nur Fatimah; Hossein Abadi, Fariba; Sankaravel, Mohansundar (Faculty of Sports Science and Recreation, 2024)
Musculoskeletal pain is a common subject of numerous studies worldwide, encompassing various populations, including university students. However, the extent of musculoskeletal pain (MSP) among university students in Malaysia remains understudied. Therefore, the main objective of this study is to determine the pattern of musculoskeletal pain among university students. A cross-sectional study was conducted among university students using an online survey. The participants were university students who volunteered and completed a structured questionnaire on MSP in the past 7 days and 12 months, as well as questionnaires on postural awareness using the Nordic Musculoskeletal Questionnaire (NMQ) and the Postural Awareness Scale Questionnaire (PAS). A total of 110 public university students, with an average age of 22.38 (1.27) years and a BMI of 23.32 (4.45) kg/cm2, participated in the study, with 43.60% being male and 56.40% female. The total PAS score was 49.46 (8.91). The prevalence of body pain was highest in the lower back and shoulders, in both the 12 months and the last 7 days. Female students reported more cases of musculoskeletal pain compared to male students, and the pattern of pain differed between genders. The PAS score showed a significant correlation with neck (r = 0.24, p = 0.01), upper back (r = 0.21, p = 0.02) (12 months), and ankle/feet (r = 0.10, p = 0.04) (last 7 days) pain. The present study indicated a weak correlation between PAS and the prevalence of MSP. Further large-scale studies are needed to investigate other contributing risk factors of MSP among university students.